Razvoj zakonodaje - Krmelj, Vlasta (Geografski obzornik, 2006)
The holistic and profound understanding of the environment is necessary for the awareness of the importance of the soil protection. Therefore the development of the rules for soil protection has started in the last ten years. Indirect soil protection has been going on since World War II within the protection of agricultural land for food production. The new policy for protection of the soil itself is needed. Such legislation should not replace current regulations which already contribute to soil protection, but rather act as an umbrella to ensure the integral and sustainable soil management.
Keywords: pedogeografija; prst (pedologija); tla; varstvo okolja; varstvo narave; environmental protection; pravna ureditev; Slovenia; Slovenija; Europe; Evropa